BioVizSeq: an R package for visualization the element on bio-sequences - Zhao, Shiqi; Zhang, Runqi; He, Maoqiu; Shui, Bonian; Zhang, Yu (Frontiers in Plant Science, 2025)
The identification and visualization of functional elements within biological sequences offers visual presentation for biologists to integrate annotation, and also helps them to produce high-quality figures for publication. Although there are now some standalone tools that can perform this function, these tools generally lack flexibility and cannot meet personalized needs. Based on the advantages of R language in graphic display, we have developed an R package: BioVizSeq (CRAN: https://cran.r-project.org/package=BioVizSeq. Github: https://github.com/zhaosq2022/BioVizSeq). It is designed for visualizing the types and distribution of elements within bio-sequences. These data could come from users or analysis programs, such as, GFF/GTF, MEME, SMART, Plantcare, PFAM, CDD and etc. BioVizSeq can be conducted locally or online, providing great convenience for researchers without coding training. Its user-friendly visualization function can simultaneously meet users’ general needs and personalized exploration.